Politics in Gotham City: The Ideological Discourse of Christopher Nolan’s Batman Trilogy - Muñoz González, Rodrigo (2026)
This article analyzes Christopher Nolan’s Batman trilogy (2005–2012) through critical discourse analysis to uncover its ideological operations. Through a qualitative matrix, the identity, objectives, and actions of both Batman and his antagonists were analyzed by identifying the ideologemes that structure the narrative. The findings reveal a defense of the status quo: Batman, a philanthropic hero of oligarchic origins, restores order and property through authoritarian exceptions and the production of symbols. Villains embody critiques of order, capital, and the political system, recoded as “external” threats and chaos. A moral geography of class emerges —virtue flowing downward, criminality rising upward— and deploy an invasion metaphor that personalizes evil while masking structural causes. The article concludes that the trilogy promotes civic rather than political awareness and calls for extending analysis to production, consumption, and materiality for future research.